Human microbiota: determining dietary factors on the journey from infants to adults - Khine, Wei Wei Thwe (fi=Turun yliopisto|en=University of Turku|, 2022)
The human microbiota profile changes with age from birth. The early colonisers of the infants’ guts are vital for their current health and also that in later ages of their lives. Determining factors affecting gut microbiota composition across ages are also critical. The thesis aims to understand gut microbiota composition from infants to adults and access to diet as its major modulating factor in healthy children and adults. Faecal microbiota was assessed using 16s rRNA amplicon sequencing in the motherchild pairs (less than one month-48 months in Study I), children (7-12 years in Study II), and adults from two dietary intervention studies (18-40 years in Study III and IV). The first study in this thesis revealed that transmission of the unique gut microbiota, Prevotella, from Indonesian mothers to their infants was successfully established but developed slowly after the weaning period when the infants’ gut microbiota, Bifidobacterium profile, changed to the adult-type, Prevotella. The weaning period (6-12 months old) is a remarkable period of alteration of gut microbiota, the immune responses (cytokines), and bile acids metabolism. After this, the diet is the primary factor influencing the gut microbiota of children. The second study disclosed that geographical location varies the gut microbiotas of Chinese and Malay children from China and two Malaysian cities into two clusters (Bacteroides and Prevotella). The location differences uncovered that the diet is the key influencing factor but not ethnicity. The third study showed that the gut microbiotas of Singaporean young adults could be divided into three clusters (Bacteroides, Prevotella, and Blautia) based on their dietary habits. The Blautia cluster (having randomly rotating Western/Southeast Asian foods) benefited from downregulated immune-regulation without changing its enterotype after the consumption of Lactobacillus-administered milk drink. The Bacteroides cluster resisted changing its enterotype and had a very slight response regarding the alteration of cytokine. The Prevotella cluster decreased its enterotype with upregulated (anti-inflammatory cells) and balanced immunoregulation. The final study found that the abundance of Bacteroides in the gut of Singaporean adults was significantly reduced following a polyphenol-rich meal containing mixed spices. Notably, the abundance of Bifidobacterium was enhanced after a meal with a high-dose of spices. Understanding gut microbiota development in infants, children, and adults and modifying its composition with beneficial microbes (probiotics) and polyphenols may promote the design of new dietary regimens and foods. These may have beneficial effects on health.

Ihmisen mikrobisto: koostumukseen vaikuttavia ravitsemustekijöitä lapsista aikuisiin Ihmisen mikrobistoprofiili muokkautuu syntymässä ja vaiheittain sen jälkeen. Lapsen suoliston varhainen kolonisaatio on merkittävä myöhemmän terveyden kannalta. Suoliston mikrobiston koostumukseen vaikuttavat mm. lapsen ikä, syntymätapa, ympäristötekijät ja ravinto. Tämän tutkimuksen tavoitteena oli karakterisoida suoliston mikrobiston koostumus, sen muutokset ja ravintotekijöiden vaikutus eri ikäkausina. Mikrobistomääritykset tehtiiin 16s rRNA amplicon sekvensointia käyttäen. Tutkittavia olivat osatutkimuksessa I äiti-lapsi parit (lapset 1-48 kk), osatutkimuksessa II lapset (7-12 v) ja osatutkimuksissa III ja IV aikuiset (18-40 v). Ensimmäisessä tutkimuksissa todettiin, että Indonesialaisila äideillä vallitseva mikrobisuku on Prevotella, joka siirtyy herkästi lapselle imetyksen aikana. Vieroituksen jälkeen siirtymä aleni nopeasti. Samanaikaisesti imeväisikäisten lasten bifidobakteeri-valtainen mikrobisto muuttui vieroituksessa (6–12 kk) aikuisten kaltaiseksi. Vieroituksen jälkeen ruokavalio oli keskeinen pikkulasten suoliston mikrobiston muokkaaja. Toinen tutkimus osoitti että maantieteellinen sijainti muodosti merkittävän ympäristö- ja ravitsemustekijän: Kiinasta ja kahdesta Malesian kaupungista kotoisin olevien kiinalaisten ja malaiji-lasten mikrobiston havaittiin jakaantuvan Bacteroides- ja Prevotella-klusteriin. Kolmas tutkimus osoitti Singaporen nuorten aikuisten suoliston mikrobiston jakautuvan kolmeen klusteriin (Bacteroides, Prevotella ja Blautia) ja ruokailutottumukset vaikuttivat merkittävästi mikrobiston kehittymiseen. Blautia-klusteri (assosioitui satunnaiseen länsimaisten ruokien käyttöön) vaikutti seerumin sytokiinivasteisiin. Suoliston mikrobiston enterotyyppi ei muuttunut tutkimuksessa, jossa nuoret nauttivat probioottisella laktobasillilla fermentoitua maitojuomaa. Neljäs osatutkimus paljasti Bacteroidesbakteerien määrä singaporelaisten aikuisten suolistossa vähenevän merkittävästi ateriaan liitetyn polyfenolipitoisen mausteseoksen nauttimisen jälkeen. Erityisesti bifidobakteerien määrä lisääntyi suurten mausteannosten jälkeen. Väitökirjatutkimuksen perusteella imeväisten, lasten ja aikuisten suoliston mikrobiston kehityksen tarkempi tunteminen ja koostumuksen muokkaaminen hyödyllisillä mikrobeilla (probiooteilla) ja polyfenoleilla mahdollistaa mikrobistoa muokkaavia ruokien kehittämisen ja ruokailutottumuksien seurannan. Nämä muutokset voivat edistää terveyttä.